Analisis Du Pont System dalam Mengukur Kinerja Keuangan Perusahaan (Studi Kasus pada Perusahaan Telekomunikasi yang Terdaftar di Bursa Efek Indonesia Periode 2012-2014) - Rosmiati Tarmizi; Merlinda Marlim (Jurnal Akuntansi dan Keuangan, 2016)
The purpose of this study is for analyzing the financial performance use the analysis Du Pont System in Telecommunication Company listed on the Indonesia Stock Exchange. Du Pont Systemanalysis is an analysis provides information on the factors that led to the rise and fall the company financial performance shows the relationship between Net Profit Margin, Total Assets Turnover and Return on Investment to determine the Return on Equity of the company. This research uses descriptive research. The data used is secondary data. Data collection methods used in this research is the method of documentation or literature study.  The analysis technique used is descriptive qualitative analysis. Based on the results of this study concluded that financial performance of the Telecommunication Company listed on the Indonesia Stock Exchange 2012-2014 period is that the financial performance is generally not good because as the value of Return on Investment  and Return on Equity is negative and even below the industry standard, except  PT. Telekomunikasi Indonesia, Tbk  financial performance is quite good for the value of Return on Investment and Return on Equity positive, although below the industry standard. Therefore, the company must improve the performance of the company, in order to achieve the company's financial performance above industry standards.